Short Communication: Dugong dugon Müller, 1776 (Sirenia, Dugongidae) in Bangka Island, Indonesia - RANDI SYAFUTRA; WAHYU ADI; MUHAMMAD IQBAL; INDRA YUSTIAN (Society for Indonesian Biodiversity, 2018)
Syafutra R, Adi W, Iqbal M, Yustian I. 2018. Short communication: Dugong dugon Müller, 1776 (Sirenia, Dugongidae) in Bangka Island, Indonesia. Biodiversitas 19: 823-830. Dugong dugon is a marine mammal species classified as Vulnerable. It has distribution in Indonesia, especially in Bangka Island. However, only four records of dugong were reported in Bangka Island in 1976, 2006, and 2007. In addition, there is little published information about local beliefs toward dugong and awareness actions toward dugong conservation in Bangka Island. This research compiled new records of dugong, local beliefs toward dugong, and awareness actions toward dugong conservation in Bangka Island. Sixteen new records of dugong were collected in Bangka Island leading to a total of 18 records for this island. All new records of dugong were obtained entirely from the eastern waters of Bangka Island. The new records also informed that most of the dugongs were found dead and entangled in gill nets. In addition, an interesting local belief caused Kurau Village becomes the most important location for fishermen to sell dead dugongs or dugongs’ meat. Furthermore, three main awareness actions toward dugong had been implemented in Bangka Island in 2017.